Increased Left Inferior Temporal Gyrus Was Found in Both Low Function Autism and High Function Autism - Cai, Jia; Hu, Xiao; Guo, Kuifang; Yang, Pingyuan; Situ, Mingjing; Huang, Yi (Frontiers in Psychiatry, 2018)
Previous neuroimaging studies of autism spectrum disorder (ASD) have focused on subjects with IQ > 70 or ASD without considering IQ levels. It remains unclear whether differences in brain anatomy in this population are associated with variations in clinical phenotype. In this study, 19 children with low functioning autism (LFA) and 19 children with high functioning autism (HFA) were compared with 27 healthy controls (HC). We found increased gray matter volume (GMV) in the left inferior temporal gyrus in subjects with both HFA and LFA and increased GMV of left middle temporal gyrus BA21 was found only in the LFA group. A significant negative correlation was found between the left inferior temporal gyrus (LITG) and the score of repetitive behavior in the HFA group.